Net present value and payback period: Malaysian Companies Preference / Siti Fatimah Abdullah - Abdullah, Siti Fatimah (1992)
The aim of this paper is to explore the subject, of capital investment appraisal from theoretical angle and further to access the extent of its practical usage by a selected public listed companies in Malaysia. Although this paper has been written mainly for the examination purpose, it will also interest those who wish to know more about, the subject of capital budgeting and decision making, its terminology, selective approaches and respective merits on investment.